2014
DOI: 10.1016/j.bjane.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the conventional CMAC and the D-blade CMAC with the direct laryngoscopes in simulated cervical spine injury—a manikin study

Abstract: The overall performance of the conventional CMAC blade proved to be the best when compared with the D-blade CMAC, Macintosh blade and the McCoy blade for intubation in simulated cervical spine patients by anesthesia residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 25 publications
1
19
0
1
Order By: Relevance
“…Requirement of optimisation maneuvers (BURP or second assistant) was least in the C-MAC video laryngoscope group in a similar study during intubation with conventional Macintosh and McCoy blades when compared with C-MAC video laryngoscopes and C-MAC -D blades. 10 In the same study, time taken for successful intubation was much less with the direct laryngoscopy which was attributed to the familiarity of the participants to those conventional scopes than to the newer video laryngoscopes. 10 Similar study was undertaken which concluded that C-MAC required shorter intubation time and fewer intubation attempts when compared with McGrath video laryngoscopes in anticipated difficult airway patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Requirement of optimisation maneuvers (BURP or second assistant) was least in the C-MAC video laryngoscope group in a similar study during intubation with conventional Macintosh and McCoy blades when compared with C-MAC video laryngoscopes and C-MAC -D blades. 10 In the same study, time taken for successful intubation was much less with the direct laryngoscopy which was attributed to the familiarity of the participants to those conventional scopes than to the newer video laryngoscopes. 10 Similar study was undertaken which concluded that C-MAC required shorter intubation time and fewer intubation attempts when compared with McGrath video laryngoscopes in anticipated difficult airway patients.…”
Section: Discussionmentioning
confidence: 91%
“…10 In the same study, time taken for successful intubation was much less with the direct laryngoscopy which was attributed to the familiarity of the participants to those conventional scopes than to the newer video laryngoscopes. 10 Similar study was undertaken which concluded that C-MAC required shorter intubation time and fewer intubation attempts when compared with McGrath video laryngoscopes in anticipated difficult airway patients. 1 A study comparing the time required for successful intubation with Airtraq laryngoscope (38±18secs) and KVL (26±11secs) proved KVL to be more efficient.…”
Section: Discussionmentioning
confidence: 91%
“…The 40º curvature of the blade D-Blade contrast with 18º of traditional McIntosh blade [8], favoring a more anterior location of the tip of the blade with an anterior displacement of the vallecula [22]. This creates a distension of the supra-glottis structures below the blade, visually separating the glottis and facilitating the differentiation, increasing the success rate.…”
Section: Discussionmentioning
confidence: 99%
“…VL in patients with cervical pathology can match or exceed the success rate of direct laryngoscopy, using comparable times and possibly reducing extension of the CS [8]. The …”
Section: Introductionmentioning
confidence: 95%
“…New devices such as videolaryngoscopes present challenge in everyday work of anesthesiologist, especially in cases where diffi cult airway management may be expected [1][2][3][4][5][6] . Despite growing popularity of these devices, only few studies evaluating D-blade videolaryngoscope performance have been conducted to date [7][8][9][10][11][12] . Th e aim of this study was to compare C-MAC D-blade with Macintosh laryngoscope in terms of glottis view, time to intubation, intubation diffi culty score (IDS) and hemodynamic stability in patients with normal airway scheduled for elective surgical procedure.…”
Section: Introductionmentioning
confidence: 99%